Evaluation of the Impact of Smart Technology on Business Decision Making in Islamic Organizations - Risqullah Firdaus Risqu; Muhammad Irwan Padli Nasution (Yayasan Bayt Shufiya Nusantara, 2025)
Advancements in artificial intelligence (AI) and management information systems have significantly transformed the way modern organizations make strategic and operational decisions. Intelligent technologies enable large volumes of data to be processed rapidly and accurately, allowing leaders to rely on more precise, data driven insights. Through AI based analytics, managers can interpret market trends more effectively, assess business performance in real time, and identify potential opportunities with greater confidence. Automation of routine tasks and the integration of predictive analytics not only accelerate decision making processes but also enhance the quality, reliability, and consistency of the decisions produced. These technological developments contribute to meaningful strategic advantages, including increased productivity, reduced operational costs, improved customer experience, and stronger competitiveness in dynamic business environments. However, despite the substantial benefits offered, organizations still encounter various challenges in implementing intelligent systems. Concerns related to data security, privacy protection, ethical implications, and the readiness of human resources and technological infrastructure remain critical issues that need careful attention. Ensuring responsible, sustainable, and well managed adoption of AI is essential so that organizations can fully harness its potential while minimizing risks that may arise in the process.